The Concept of Prohibiting "Approaching Adultery" and Efforts to Avoid it from the Perception of Generation Z - Himmatul Khoiroh (An-Nur International Journal of Islamic Thought, 2023)
This research represents the concept of prohibiting "approaching adultery" and efforts to stay away from it, according to the perception of Generation Z (often shortened to Gen Z), colloquially known as Zoomers. Currently, there is a proliferation of relationships between men and women who have feelings of love but without marital status. This research uses qualitative methods with the type of field research or field research with data collection techniques carried out using interviews and questionnaires. This research was conducted by several respondents in various areas in Sidoarjo, including Sidoarjo, Sukodono, and Prambon subdistricts. The statements used during the interview show that Generation Z has different views regarding the prohibition on approaching adultery. Generation Z, who are firm in their stance with the thoughts and knowledge gained in Islamic Boarding Schools and a supportive environment, will not influence their views regarding the prohibition of adultery, even though Generation Z is developing in a world of technology that is developing rapidly, most of them have a circle that builds a good identity.  On the other hand, Generation Z, who have a non-Islamic boarding school background, feel that behavior approaching adultery is normal.